Nano‐Pulse Stimulation Induces Changes in the Intracellular Organelles in Rat Liver Tumors Treated In Situ. Issue 9 (27th March 2020) - Nuccitelli, Richard; McDaniel, Amanda; Connolly, Richard; Zelickson, Brian; Hartman, Holly
Abstract : Background and Objectives: Nano‐pulse stimulation (NPS) therapy is the application of ultrafast pulses of high amplitude electrical energy to tissues to influence cell function. Unique characteristics of these pulses enable electric field penetration into the interior of cells and organelles to generate transient nanopores in both organelle and plasma membranes. The purpose of this study is to document the temporal and physical changes in intracellular organelles following NPS therapy using electron microscopy. Study Design/Materials and Methods: Liver tumors were induced in five buffalo rats by implanting syngeneic McA‐RH7777 hepatocellular carcinoma cells into the surgically exposed livers. Tumors were allowed to grow for 1 week and then the surgically exposed livers were treated in situ with NPS energy delivered at a sufficient level to trigger regulated cell death in the tumor. Samples of NPS‐treated and control tissue were removed and fixed for electron microscopy at 1 minute, 5 minutes, 30 minutes, 2 hours and 4 hours after exposure. Results: Measurements of cellular organelles indicate strong swelling following NPS therapy exposure compared with untreated controls. The mean diameter of the mitochondria increased by 55% within 1 minute and then by 2.5‐fold by 2 hours post‐NPS therapy. The rough endoplasmic reticulum (RER) cisternae swelled immediately after NPS therapy with reduced swelling by 30 minutes and loss of structural integrity by 2 hours. The Golgi apparatus appears swollen in images collected 1 and 5 minutes after NPS therapy and was no longer detected at 30 minutes and 2 hours post‐NPS therapy. By 4 hours after NPS therapy, a nascent Golgi apparatus was detected in many of the images. The plasma membrane lost its well‐defined morphology and became less linear, exhibiting discontinuities as early as 1 minute post‐NPS energy exposure and the nuclear envelope became subjectively less distinct over time. Conclusions: NPS therapy at sufficient energy levels causes the rapid swelling of organelles, disintegration of the RER, breaks in the plasma membrane and blurs the borders of the nuclear envelope. These changes in the mitochondria and RER are indicative of a regulated cell death process. These immediate physical changes to vital cell organelles are likely to trigger subsequent regulated cell death mechanisms observed in other studies of NPS therapy. Lasers Surg. Med. © 2020 The Authors. Lasers in Surgery and Medicine published by Wiley Periodicals, Inc.